A Novel Kumaraswamy-Fréchet Poisson Distribution (Contemporary Mathematics, 2025)
This paper introduces a novel probability distribution by combining the Kumaraswamy-G-Poisson and Fréchet distributions, resulting in the six-parameter Kumaraswamy-Fréchet Poisson (KFP) distribution. The proposed model enhances flexibility for modeling diverse data types beyond traditional lifetime applications. We rigorously derive its key statistical properties and estimate parameters using Maximum Likelihood Estimation (MLE). To demonstrate its effectiveness, we apply the KFP distribution to real-world data, showing satisfactory goodness-of-fit when compared with competing distributions.
Keywords: fréchet distribution, hazard rate function, maximum likelihood estimate, moments, quantile function